Academic Supervision For Enhancing Teachers’ Pedagogical Competence: A Case Study at SD Negeri Tanjung Lama, Aceh Tenggara, Indonesia - Ramlan Ramlan (Yayasan Madinah Al-Aziziyah, 2025)
Improving teacher pedagogical competence remains central to global educational reform. Academic supervision has been widely recognized as a strategic instrument for strengthening instructional quality; however, its contextual implementation in rural developing-country settings remains underexplored. This study investigates how academic supervision contributes to improving teachers’ pedagogical competence in a rural public elementary school in Aceh Tenggara, Indonesia. Employing a qualitative case study design, data were collected through semi-structured interviews, classroom observations, and document analysis involving one principal and six teachers. Thematic analysis revealed that structured supervision planning, dialogical feedback processes, reflective post-observation conferences, and continuous mentoring significantly enhanced lesson planning quality, student-centered learning practices, classroom management, and formative assessment strategies. Nevertheless, supervision effectiveness was constrained by administrative workload, time limitations, and limited professional development integration. This study contributes theoretically by contextualizing instructional supervision theory within rural school leadership practice and practically by proposing a contextual supervision improvement model applicable to similar settings. The findings underscore the need for policy reinforcement to institutionalize reflective supervision frameworks in primary education systems.